(untitled) (Journal of the College of Basic Education, 2022)
The new Co(II), Cu(II), Zn(II) and Cd(II) complexes with a multidentate Schiff-base ligand [Benzen1,4-dicarboxaldehyde bis-Semicarbazone] [H2L] are reported. The ligand H2L was derived from the condensation reaction of Benzen1,4-dicarboxaldehyde and Semicarbazidehydrochloride. The complexes were prepared from the reaction of the corresponding metal chloride with the ligand. The ligand and its metal complexes were characterised by spectroscopic methods (FTIR, UV-Vis,1H NMR, A.A), chloride content, conductance and melting point measurements. These studies revealed complexes of the general formulae [M2(L)2] with tetrahedral geometries for CoII, ZnII and CdII complexes while square planar geometries have been suggested for CuII complex. Biological activity of the ligand and its metal complexes against gram positive bacterial strain Bacillus (G+) and gram negative bacteria Pseudomonase (G-) revealed that the metal complexes become less resistive to the microbial activities as compared to the free ligand.